Simple evaluation method of adhesive failure criterion in multiaxial stress states by uniaxial tensile tests - Masato IIMORI (The Japan Society of Mechanical Engineers, 2018)
We propose a simple tensile test with which to identify the parameters that constitute the failure criterion of an adhesive in a multiaxial stress state. In this paper, we define the failure criterion as the proportional limit of load-displacement curves obtained from experiments. We first introduced the failure criterion based on the first invariant of the stress tensor and the second invariant of the deviatoric stress tensor. To determine the unknown parameters of the failure criterion, two experiments were performed. The first was a tensile shear test for bonded plate structures to obtain the strength of the adhesive material in simple shear deformation and assess how the strength depends on the strain rate and adhesion layer thickness. We subsequently performed a uniaxial tensile test for circular pipe specimens bonded by the same adhesive. The pipe specimens had inclined cutting surfaces for the purpose of measuring adhesive failure points in a multiaxial stress state. Using the failure criterion with the developed tensile test, we next evaluated the adhesive strength of the pipe specimens with reference thickness of h* ~ 0.4 mm. Formulating a scale function δ as a reference of h*, we calculated the failure magnitudes of pipe specimens with different thicknesses h. As a result, we obtained the power law of δ ∝ h−0.79, which allows us to extend the failure criterion to different thicknesses of the adhesive layer.